Modeling and evaluation of political processes: A new quantitative approach - Christian H. C. A. Henning (Kiel University, Department of Agricultural Economics, Chair of Agricultural Policy, 2015)
At the academic level and in political practice, participatory and evidence-based political processes are increasingly recognized as mechanisms that guarantee more efficient political decisionmaking. However, no theoretical framework that allows a clear definition of participatory and evidence-based policy processes and demonstrates the positive impact of these processes on political performance is currently available. In addition, no operational approach that allows for the empirical measurement and characterization of these processes currently exists. In this context, this chapter develops the evolutionary computable general political economy equilibrium model (eCGPE) as a theoretical framework and an empirically applicable tool for defining, evaluating and designing efficient participatory and evidencebased policy processes. We further demonstrate that based on the eCGPE approach, a political diagnosis can be made (i.e., political performance gaps can be identified). Furthermore, a political therapy (i.e., a set of adequate strategies for reducing existing performance gaps) can be derived via simulation analyses that are based on the eCGPE.
Keywords: 330; Political processes; political economy modeling; agricultural policy; CAADP; Malawi; Africa